Honey Hunt. 4 - Aihara, Miki (Shojo beat manga, 2010)
"As Yura continues her foray into the glamorous world of acting, she's starting to learn that success is often marred with setbacks and compromises. Although she fails to land the lead role in a new drama penned by famous screenwriter Maki Todo, she does succeed in getting offered the part of the heroine's friend. However, her boss Keiichi cautions Yura that her increasing popularity will result in greater scrutiny of her privated life by the paparazzi. Can Yura continue growing as an actress while keeping her budding relationships with Q-ta and Haruka in check?"--Back cover.